Relationship Marketing sebagai Upaya untuk Mempertahankan Loyalitas Pelanggan: - Farah Chalida Hanoum; Yanti Hasbian Setiawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
Relationship marketing establishing, developing and maintaining succesful relational exchanges constitutes a major shift in marketing theory and practice. Relationship marketing refer to all marketing activities directed toward establishing, developing and maintaining succesful relational exchanges.